Morbidity pattern and nutritional status of Anganwadi students in a selected gram-panchayat in Tripura, India - Das, Dipak Kumar; Ladku, Jadav Vishal (International Journal Of Community Medicine And Public Health, 2024)
Background: Early childhood care and development (ECCD) was a critical foundation for overall growth and development, not only of children but society on the whole which has severely neglected in India. According to NFHS almost half of all children under three were underweight. Prevalence of acute illness at the household level in Tripura was 12%. It is needed to draw the attention of people towards the person possessing nutrition and morbidity. The objectives of this study is to assess the nutritional status, prevalence of major morbidities and examine the impact of socio-demographic factors on nutritional status and morbidities in a block under study in Tripura. Methods: In 2023 after receiving approval from KJSCE, IGNOU study centre, Mumbai, selected anganwadi students of Mechuria gram-panchayat of Tripura state were surveyed. We utilised Univariate, Bivariate and chi-square methods for this study. Results: In Mechuria gram-panchayat 21% anganwadi students were underweight, 10% were obese and 57% Anganwadi students were suffered from acute illness. Common cold was 70% which was the highest prevalence. Major health problems were decreased with increasing parent’s age and their education and also raise this health problem with increasing age of Anganwadi teachers and helpers. It may be due to overburden of their other responsibilities. Conclusions: Common cold, underweight and obese were the major health problem and government hospital played the main role in providing treatment facility in this village. Limitation of this study included that this study based on self-reporting.